Nordhaus on philosophy in climate change economics - Laurent JODOIN (The Journal of Philosophical Economics, 2020)

(untitled)
Nordhaus’ contribution to climate change economics is well-known and, for many, praiseworthy. But his refusal to acknowledge his normative stances is philosophically problematic. This article explores his arguments about philosophy in the economics of climate change found in his review of the Stern’s Review (2007). It concludes that Nordhaus nonetheless relies on normative, ethical assumptions, whose oversight hinders the finding of a solution to the problems he tries himself to solve.